Epidemiology of lung cancer in the period from 1993 to 2002 in Konin and Pila, cities with discrete industrial-geographic structure - Nowicki, Andrzej; Kowalska, Jolanta (Contemporary Oncology/Współczesna Onkologia, 2007)
Introduction: Bad prognosis and permanent increase in the number of cases makes lung cancer the biggest problem of contemporary oncology. Scientific investigations prove that cigarette smoking is responsible for 80% of all cases of lung cancer. Continuous growth of morbidity and mortality rate of lung cancer is observed commonly. The aim of this paper was the comparative analysis between morbidity and mortality of lung cancer in Konin and Piła from 1993 to 2002 concerning industrial and also geographical factors. Material and methods: Data were subjected to the analysis of registered diseases and mortality of lung cancer in Konin and Piła from 1993 to 2002. Data were obtained from three different secondary sources. Information about demographic structure in Konin and Piła was received from the Regional Data Bank of the Statistical Office. The number of illnesses and deaths from lung cancer in the population of both cities was received from public accessible reports of the Oncology Center and from the Tumour Register in Poznań. Results: Growing morbidity and cases of death from lung cancer among women was affirmed in both cities. In the analyzed decade (1993-2002) morbidity rate of lung cancer rose among women aged 65 or more. This derives from the fact that women who were born between 1940 and 1960 fall in the age of greater risk of disease, who were exposed to the greatest level of risk from tobacco smoke. Taking into account the number of deaths caused by lung cancer during the period of 1993-2002 it appears that the number of deaths per 100 000 inhabitants was constantly rising in Konin and Piła. The differences were not statistically significant regarding age and sex. In reference to women, an increasing number of deaths was observed in Piła, and the inverse situation was observed when men were considered. Conclusions: Neither industrial nor geographic structures had any essential influence on the frequency of disease. It can be assumed that the major cause of lung cancer is tobacco smoke and not the level of industrialization. In the last decade (1993-2002) a clear rise in morbidity and deaths from lung cancer was observed in both cities. The majority of people who suffered from lung cancer were men older than 65. The number of diseases and deaths per 100 000 inhabitants was similar in both cities and the differences were not statistically significant.